EXPLORING THE SIGNIFICANCE OF KINSHIP TERMINOLOGY IN A SPECIFIC SOCIAL AND CULTURAL SYSTEM - Dalila LALAOUNA; Ammar SIDIDRIS (Social Sciences and Education Research Review)
Kinship is considered a fundamental gateway to understanding patterns of social, cultural, and organizational interaction. The kinship term also represents a crucial structure within the prevalent kinship system in society. It reveals classifications related to relatives, defining their statuses and relationships with each other. Relationships among relatives, such as marriage, role distribution, positions, orphan care, inheritance distribution, and others, take into account the type of kinship and the nature of the specific kin identified by the kinship term. As a result, one can question the patterns of use and deployment of the kinship term in the social and cultural system.